1994
DOI: 10.1002/eji.1830240523
|View full text |Cite
|
Sign up to set email alerts
|

Clonal expansion of T lymphocytes causes arthritis and mortality in mice infected with toxic shock syndrome toxin‐1‐producing staphylococci

Abstract: Erosive arthritis is a common and feared complication of staphylococcal infection. The reason(s) for the progressive course of the arthritis is unknown. It has been recently established that enterotoxins produced by Staphylococcus aureus display superantigen properties leading to stimulation of T cells carrying distinct T cell receptor V beta elements. This finding provides a potential connection between staphylococcal exoproteins and endogenous immune mechanisms participating in the infectious process. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 33 publications
0
66
1
Order By: Relevance
“…MHC class II molecules could influence immune responses to staphylococci through their role in shaping the repertoire of mature T cells during T cell development [1], thus favouring the existence of pathogenic T cells. We have previously demonstrated that CD4 þ Vb11 þ TCR-expressing lymphocytes are of pathogenic significance in S. aureus-induced arthritis, since mice depleted of these cells displayed a lower frequency of disease [5]. In this respect, it is difficult to explain the differences between the groups of mice used in the present experiments through this mechanism, since there was no difference in the number of Vb11 þ cells in the inflamed joints between the groups.…”
Section: Discussionmentioning
confidence: 67%
“…MHC class II molecules could influence immune responses to staphylococci through their role in shaping the repertoire of mature T cells during T cell development [1], thus favouring the existence of pathogenic T cells. We have previously demonstrated that CD4 þ Vb11 þ TCR-expressing lymphocytes are of pathogenic significance in S. aureus-induced arthritis, since mice depleted of these cells displayed a lower frequency of disease [5]. In this respect, it is difficult to explain the differences between the groups of mice used in the present experiments through this mechanism, since there was no difference in the number of Vb11 þ cells in the inflamed joints between the groups.…”
Section: Discussionmentioning
confidence: 67%
“…Earlier studies have demonstrated the pivotal role of CD4 þ T cells in the progression of septic arthritis [8,9]. In the light of a recent report demonstrating that NK cells can play an important role in down-regulating Th1-mediated experimental colitis by controlling the responses of effector T cells to gut bacteria [28], we analysed the effect of in vivo NK cell depletion on T celldependent inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of lymphocytes in disease development has been extensively studied. Abdelnour et al have shown that T lymphocytes play a major pathogenic role in the disease [8,9]. Also, B lymphocytes contribute to arthritis, as shown in studies demonstrating that B cell-deficient Xid mice display a less severe arthritis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory work with mice shows that strains of Staphylococcus that produce exoproteins (i.e., enterotoxin) cause more severe arthritis in infected joints than do strains that do not produce exoproteins [3]. Following on from this, it was discovered that specific inhibition of T-lymphocyte proliferation decreases the severity of arthritis, while generalised inhibition of the immune system increases the severity of arthritis [1,2]. This leads to the possibility that bacterial antigens and bacterial exotoxins stimulate Tlymphocyte proliferation and that this can occur even though the bacteria have been killed.…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%